High Prevalence of Antimicrobial-resistant Gram-negative Colonization in Hospitalized Cambodian Infants. Issue 8 (August 2016) - Turner, Paul; Pol, Sreymom; Soeng, Sona; Sar, Poda; Neou, Leakhena; Chea, Phal; Day, Nicholas PJ; Cooper, Ben S.; Turner, Claudia
Abstract : Background: Antimicrobial-resistant Gram-negative infections are a significant cause of mortality in young infants. We aimed to determine characteristics of, and risk factors for, colonization and invasive infection caused by 3rd generation cephalosporin (3GC) or carbapenem-resistant organisms in outborn infants admitted to a neonatal unit (NU) in Cambodia. Methods: During the first year of operation, patients admitted to the Angkor Hospital for Children NU, Siem Reap, Cambodia, underwent rectal swabbing on admission and twice weekly until discharge. Swabs were taken also from 7 environmental sites. Swabs were cultured to identify 3GC or carbapenem-resistant Acinetobacter sp., Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa . Results: The study included 333 infants with a median age at NU admission of 10 days (range, 0–43). Colonization by ≥1 3GC-resistant organism was detected in 85.9% (286/333). Admission swabs were collected in 289 infants: 61.9% were colonized by a 3GC-resistant organism at the time of admission, and a further 23.2% were colonized during hospitalization, at a median of 4 days [95% confidence interval: 3–5]. Probiotic treatment (hazard ratio: 0.58; 95% confidence interval: 0.35–0.98) was associated with delayed colonization. Colonization by a carbapenem-resistant organism occurred in 25 (7.5%) infants. Six infants had NU-associated K. pneumoniae bacteremia; phenotypically identical colonizing strains were found in 3 infants. Environmental colonization occurred early. Conclusions: Colonization by antimicrobial-resistant Gram-negative organisms occurred early in hospitalized Cambodian infants and was associated with subsequent invasive infection. Trials of potential interventions such as probiotics are needed. Abstract : Supplemental Digital Content is available in the text.